Dampak Manajemen Kerja Hybrid terhadap Produktivitas dan Kolaborasi Tim - Uning Heri Gagarin; Hendri Mayanta; Obet Hendra Berutu (Jurnal Pariwisata Tawangmangu, 2025)
This study examines the impact of hybrid work management on employee productivity and team collaboration in organizations implementing a work model that combines on-site (office) and remote work. The research aims to analyze how hybrid work management affects employee productivity and team collaboration, while also identifying supporting and inhibiting factors in its implementation. The study uses a quantitative approach through surveys, complemented by qualitative analysis from literature review. One supporting study applies Structural Equation Modeling (SEM) using SmartPLS. The findings indicate that hybrid work can significantly improve productivity—up to 82.4%—when backed by appropriate management practices and adequate technology. However, several challenges need to be addressed, including ineffective communication, social isolation, unequal access to information, and difficulties in monitoring performance. The study suggests that managers should conduct routine check-ins, leverage collaboration technologies, set clear expectations and work targets, and prioritize employee well-being to maintain team cohesion in hybrid working arrangements.